Factors affecting occlusion pressure and ischemic preconditioning - Brown, H.; Binnie, M. J.; Dawson, B.; Bullock, N.; Scott, B. R.; Peeling, P. (European Journal of Sport Science, 2018)
Purpose: To determine the effect of limb selection (upper/lower), cuff width (small (6 cm)/medium (13 cm) upper; medium/large (18 cm) lower) and anthropometry on arterial occlusion pressure (AOP) in ischemic preconditioning (IPC). Methods: Twenty athletes (10 females and 10 males) had surface anthropometry and dual x-ray absorptiometry (DXA) assessments before using Doppler ultrasound to confirm AOP for each limb. Subsequently, 5 min of occlusion occurred, with near-infrared spectroscopy (NIRS) measuring muscle oxygenation changes. Resultant AOP was compared between sexes, limbs and cuff sizes using linear regression models. Results: Mean AOP was higher in the lower limbs than the upper limbs (161 ± 18 vs. 133 ± 12 mm Hg; p < .001), and with smaller cuffs in upper (161 ± 16 vs. 133 ± 12 mm Hg; p < .001), but not lower limbs (161 ± 16 vs. 170 ± 26 mm Hg; p = .222). Sex and resting systolic blood pressure (SBP) accounted for 77% (small cuff) to 83% (medium cuff) of variance in AOP for upper limbs, and 61% (medium cuff) to 63% (large cuff) in lower limbs. Including anthropometry accounted for 82% (small cuff) to 89% (medium cuff) and 78% (medium cuff) to 79% (large cuff) of variance for upper and lower limbs, respectively. Adding DXA variables improved the explained variance up to 83% (small cuff) to 91% (medium cuff) and 79% (medium cuff) to 87% (large cuff) for upper and lower limbs, respectively. NIRS data showed significantly greater tissue oxygenation changes in upper versus lower limbs. Conclusions: The AOP in athletes is dependent on limb occluded, sex, SBP, limb and cuff size, and body composition.